1980
DOI: 10.1007/bf00835725
|View full text |Cite
|
Sign up to set email alerts
|

Anticipated and actual barriers to developing community mental health programs for the elderly

Abstract: Teams of state and local agency professionals responsible for mental health and aging services participated in a model project utilizing education and consultation to facilitate community mental health programming for the elderly. Participants identified both anticipated and actual barriers to programming. Competing program priorities and lack of staff knowledge about mental health and aging were anticipated and confirmed as major barriers. Agency-organizational barriers were unanticipated, yet there were seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1985
1985
2003
2003

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…A report on the development of a community mental health program for the elderly (Pratt & Kethy, 1980) showed that negative attitudes by older adults were encountered as an actual barrier by only half of the program planners anticipating such attitudes to be a problem. Another study (Lasoski & Thelen, 1987) compared older and younger adults in their attitudes about mental health by investigating the influence of age on views toward mental health services and intervention issues.…”
Section: Introductionmentioning
confidence: 98%
“…A report on the development of a community mental health program for the elderly (Pratt & Kethy, 1980) showed that negative attitudes by older adults were encountered as an actual barrier by only half of the program planners anticipating such attitudes to be a problem. Another study (Lasoski & Thelen, 1987) compared older and younger adults in their attitudes about mental health by investigating the influence of age on views toward mental health services and intervention issues.…”
Section: Introductionmentioning
confidence: 98%
“…Although interest group membership accounted for a small amount of variation, it has heuristic value for planning attitude change efforts because it permits more focused targeting than using demographic variables. Used judiciously, information campaigns could potentially both (a) fill knowledge gaps (lack of awareness) and (b) correct false beliefs (expectancies) about a program (Pratt & Kethley, 1980). Misperceptions (factually incorrect expectancies) accounted for about one-half of the reasons involved in attitudes unrelated to deinstitutionalization (Severy, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…The six samples were asked to what extent they considered 10 variables to be barriers to the provision of mental health services to individuals with severe physical disability. The focus on barriers was based in part on a study by Pratt and Kethley (1980) regarding barriers to developing community mental health programs for the elderly, as well as reviews of the literature and input from expert reviewers during the development of the survey methodology. Depending on the sample, there were slight variations or additions to other portions of the basic survey instrument.…”
Section: Instrumentmentioning
confidence: 99%